Gender, productivity, and promotion in the Irish economics profession - Kevin Devereux; Margaret Samahita (University College Dublin, UCD School of Economics, 2022)
Women in economics follow different career paths than men, facing differential treatment when it comes to journal acceptance as well as promotion. We focus on a selfdirected measure of productivity: working paper output. This avoids potential sex biases in the peer-review process. We find that men produce more working papers than women in Irish economics departments, and that authors with more working papers get promoted at higher rates. We do not find any differences in promotion rates by sex, whether in levels, returns to productivity, or coauthorship patterns.
Keywords: J16; J24; J71; M51; 330; Gender discrimination; promotion; research; productivity